Peran Mahasiswa MSIB Batch 4 dalam Corporate Social Responsibility Perusahaan Melalui Sembako Ramadhan Kepada Masyarakat di Sekitar PT Petrokimia Gresik - Putri Prastikasari; Siti Ning Farida (Institut Teknologi dan Bisnis Semarang, 2023)
Based on the Katadata.com survey, basic prices ahead of Ramadhan in Indonesia tend to increase as of March 17 2023. Seeing these conditions, the purpose of this community service, PT Petrokimia Gresik and its Certified Independent Study Internship students (MSIB) get around a Ramadhan Sembako program as a form of Corporate Social Responsibility (CSR) company. This program involved 6 East Java